A Bridge Approach to Fault Diagnosis in Buildings - Le, Minh Hoang; Nguyen, Trung Kien; Ploix, Stephane (Old Journal, 2017)
Nowadays, building’s power consumption represents the most important portion of the global consumption (about 40-45%). To use more efficient energy sources, it requires not only the improvement in materials as well as new technology measures using less energy, but requires also the detection of faults that can occur during building life. These faults cause not only serious energy losses, but also human discomfort in the buildings. Thanks to sensor network, discomfort or failure alarms can be detected, which identify some issues in buildings. An alarm must be analysis to identify the faults and fix them as quickly as possible in order to maintain building performance. The aim of this paper is to study for application of diagnostic theories in the building. A Bridge approach is used as a diagnosis tools in the buildings. An application to a smart building is implemented to face this fault diagnosis in buildings problem.